1990
DOI: 10.1007/bf01857784
|View full text |Cite
|
Sign up to set email alerts
|

Model simulation of parametrically excited ship rolling

Abstract: Abstract. Two different models for simulating the ship motion in longitudinal or oblique seas are presented and studied in detail. Particular attention is devoted to the parametrically induced rolling which may be established by means of the nonlinear coupling between both heave-roll and/or pitch-roll motions. It is proved that the phenomenon is likely to occur with this mechanism when the roll frequency is subharmonic of the encounter wave frequency and when the vertical motions become resonant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…which is similar to equation (7) of [18] and equation (47) of [16]. For the special case of an undamped system, the instability condition of the no-roll response is then…”
Section: Conditions For Roll Instabilitymentioning
confidence: 62%
See 1 more Smart Citation
“…which is similar to equation (7) of [18] and equation (47) of [16]. For the special case of an undamped system, the instability condition of the no-roll response is then…”
Section: Conditions For Roll Instabilitymentioning
confidence: 62%
“…This is the well-known condition for the first instability region of the Mathieu equation for the undamped case, see, e.g., [5,7,11,18]. The positive sign for the second term on the right-hand side of equation (20) is associated with the response of # with B = -C, equation (17), while the negative sign is with B = C. It can easily be shown that the maximum roll, #max, is in phase with positive z if co < cob and B = C or if co > coh and B = -C, but #max is in phase with negative z if co > cob and B = C. Another important instability region, the fundamental parametric resonance region, involves harmonic roll responses; its instability conditions can be determined by substituting the following harmonic response into equation (11).…”
Section: Conditions For Roll Instabilitymentioning
confidence: 99%
“…In the present paper some results obtained by Tondl A. and Nabergoj R. [1,2] will be extended for the case of a nonlinear elastic spring and ~onlinear expansions of trigonometric functions. …”
Section: Introductionmentioning
confidence: 93%
“…Using the Lagrange equations for the system represented in Fig.l we have the following differential equations of motion: 1) where Z = x-u is the relative vertical displacement ·of the mass Af, x i~ the vertical displacemen~ of the u1ass M from its static position of equilibrium 1 u = qcoswt is the vertical displacement of the base of the spring -masS system, pis the angular displacement of the pendulum 1 ko and {3,., are the linear and nonlinear charadeilltics of the spring respectively, l is the length of the rod, ho and Co are the damping cQefficients of the linear and angular motions, respectively, g is the gravity acceleration and an overdot denotes a derivative with respect to time t. …”
Section: Motion Equationsmentioning
confidence: 99%
See 1 more Smart Citation